Reliability of the Luganda version of the Child Behaviour Checklist in measuring behavioural problems after cerebral malaria - Opoka Robert O; Giordani Bruno; Nakasujja Noeline; Bangirana Paul; John Chandy C; Boivin Michael J (BMC, 2009)
Abstract Background No measure of childhood behaviour has been validated in Uganda despite the documented risks to behaviour. Cerebral malaria in children poses a great risk to their behaviour, however behavioural outcomes after cerebral malaria have not been described in children. This study examined the reliability of the Luganda version of the Child Behaviour Checklist (CBCL) and described the behavioural outcomes of cerebral malaria in Ugandan children. Methods The CBCL was administered to parents of 64 children aged 7 to 16 years participating in a trial to improve cognitive functioning after cerebral malaria. These children were assigned to the treatment or control group. The CBCL parent ratings were completed for the children at baseline and nine weeks later. The CBCL was translated into Luganda, a local language, prior to its use. Baseline scores were used to calculate internal consistency using Cronbach Alpha. Correlations between the first and second scores of the control group were used to determine test-retest reliability. Multicultural norms for the CBCL were used to identify children with behavioural problems of clinical significance. Results The test-retest reliability and internal consistency of the Internalising scales were 0.64 and 0.66 respectively; 0.74 and 0.78 for the Externalising scale and 0.67 and 0.83 for Total Problems. Withdrawn/Depressed (15.6%), Thought Problems (12.5%), Aggressive Behaviour (9.4%) and Oppositional Defiant Behaviour (9.4%) were the commonly reported problems. Conclusion The Luganda version of the CBCL is a fairly reliable measure of behavioural problems in Ugandan children. Depressive and thought problems are likely behavioural outcomes of cerebral malaria in children. Further work in children with psychiatric diagnoses is required to test its validity in a clinical setting.